Synthesis and electrochemical characterization of titania nano-filler embedded AgI–Ag2CO3 solid electrolyte for energy storage devices - Abjana Parbin; Shahla Imteyaz; Rafiuddin (Hybrid Advances)
This study covers the synthesis and electrochemical characteristics of a nanocomposite solid electrolyte, AgI–Ag2CO3, including TiO2 nano-filler at various weight percentages ranging from 0 to 40 wt %. A series of compositions with various weight percentages of (1-x) AgI–Ag2CO3 -(x) TiO2 samples have been fabricated by the solid-state method and characterized by FT-IR, XRD, SEM-EDX, TEM, and Impedance Spectroscopy to execute a comprehensive structural analysis of the post-synthetically modified solid electrolyte (SE). Among the various nanocomposite material compositions, 20 wt % TiO2 nanocomposite shows the highest ionic conductivity, i.e., σ = 1.159 × 10−2 Scm−1 and the lowest activation energy, 0.4789 eV at 298 K. The suggested conceptual approach was validated by the solid electrolyte's impedance, capacitance, and other structural behavior. The change in structure and morphology of the solid electrolyte has been found to be associated with the increase in conductivity, indicating that the amorphous domain is appropriate for solid-state battery applications.